Kedudukan PT. Angkasa Pura I Dalam Pembayaran Bea Perolehan Hak Atas Tanah Dan Bangunan - Ridwan HR; Nurmalita Ayuningtyas Harahap; Siti Ruhama Mardhatillah (Fakultas Hukum Universitas Islam Indonesia, 2019)
This paper examines the issues of, first, the special assignment of the Minister of BUMN (State Owned Enterprise) and the Minister of Transportation to PT. Angkasa Pura I (Persero) in land procurement forthe construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, DIY Province whether it can invalidate the obligations of PT. Angkasa Pura I (Persero) to pay BPHTB. Second, it is regarding the land procurement for the construction of the New Yogyakarta International Airport (NYIA) airport in Kulon Progo Regency, Special District of Yogyakarta whether it can be qualified as